Clinical Evaluation of the Diagnostic Role of MicroRNA-155 in Breast Cancer - Fatemeh Hosseini Mojahed; Amir Hossein Aalami; Vahid Pouresmaeil; Amir Amirabadi; Mahdi Qasemi Rad; Amirhossein Sahebkar (International Journal of Genomics)
Aim. Biochemical markers, including microRNAs (miRs), may facilitate the diagnosis and prognosis of breast cancer. This study was aimed at assessing serum miR-155 expression in patients with breast cancer and receptors. Methods. This case-control study was conducted on 36 patients with breast cancer and 36 healthy individuals. After RNA extraction from the patient’s serum, cDNA was synthesized. The expression of miR-155 was measured using RT-qPCR. Demographic and histochemical data were extracted from patient documents. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software. Results. The mean age of subjects in breast cancer and control groups was 47.64±8.19 and 47.36±7.52 years, respectively. The serum miR-155 expression was higher in the cancer group (1.68±0.66) compared to the control group (p<0.0001). There was a significant relationship between serum miR-155 expression and the tumor grade (p<0.001), tumor stage (p<0.001), and tumor size (p<0.001) of the patients. However, no relationship between miR-155 expression and the presence of lymph node involvement (p=0.15), HER2 (p=0.79), Ki-67 (p=0.9), progesterone receptor (p=0.54), and estrogen receptors (p=0.84) was found. The ROC curve analysis showed that the AUC was 0.89 (77.78% sensitivity and 88.89% specificity), and the cutoff was 1.4 (Youden index: 0.6667) for detecting breast cancer. Conclusion. The findings of this study revealed that serum miR-155 may serve as a potential noninvasive molecular biomarker for breast cancer diagnosis and can help predict the grade of the disease.